O uso de ferramentas de monitoramento na identificação dos casos prováveis de dengue no Estado da Paraíba - Oliveira, Amélia Maria Rodrigues (2019)
This study aims to identify cases of dengue in the state of Paraíba through searches performed by users, so that, collected in the tool Google Trends in real time with the aid of statistical analysis. It is known that dengue is a disease that affects more than half of the world's population, so some sources that are responsible for disclosing the cases of this disease delay a period to be disseminating graphics, data and information. Thus, it is reflected in limited and slow information since much of this information depends on public health facilities such as hospitals that rely on traditional methods. With this problem in mind, it was made possible to make use of the tool Google Trends in real time, because through user searches generate sources of data and information to track infectious diseases around the planet through these searches performed by users . These traces through searches conducted through statistical analysis will help to understand the resulting data so that the factors and indications of dengue cases in the state of Paraiba can be known. In this dissertation, data collection was applied by applying the correlation of statistical analyzes so as to result in a significance of identifying the probable cases of dengue in the state of Paraíba during the last 10 years (2008-2017).